2017
DOI: 10.1007/s00244-017-0422-9
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Fate of Organic and Organometallic Pollutants in Municipal Wastewater Treatment Plants and Their Impact on Receiving Waters (Adour Estuary, France)

Abstract: To achieve a "Good Environmental Status by 2015," as demanded by the water framework directive, monitoring programs are needed to furnish data on target compounds. In this study, a first evaluation of influents and main emissions of 3 local wastewater treatment plants (WWTP) in the Adour estuary (southwest of France) was performed for 23 pollutants (10 musk fragrances, 5 alkylphenols, and 8 organometallics), as well as receiving estuarine water from the same area. High frequency of occurrence of these compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…5) but they are only two to three times higher than the background values (Table SI-4) and have no great impact on estuarine water. Similarly, local wastewaters can be sources of musks and alkylphenols to Adour Estuary but have limited effect due to contaminants reactivity and a large dilution of these anthropogenic tributaries (Cavalheiro et al, 2017). The effect separation of Sal/T and SPM/IHg D also shows concentrations of MeHg D in STP that are higher than expected, despite higher concentrations of SPM (Figs.…”
Section: Tablementioning
confidence: 85%
See 1 more Smart Citation
“…5) but they are only two to three times higher than the background values (Table SI-4) and have no great impact on estuarine water. Similarly, local wastewaters can be sources of musks and alkylphenols to Adour Estuary but have limited effect due to contaminants reactivity and a large dilution of these anthropogenic tributaries (Cavalheiro et al, 2017). The effect separation of Sal/T and SPM/IHg D also shows concentrations of MeHg D in STP that are higher than expected, despite higher concentrations of SPM (Figs.…”
Section: Tablementioning
confidence: 85%
“…The Adour Estuary (SW France) is medium size dynamic mesotidal estuary. Its urban/industrial downstream part is deteriorated due to numerous anthropogenic impacts (SDAGE-PDM, 2014;Cavalheiro et al, 2017). Both surface sediments (Stoichev et al, 2004) and water (Stoichev et al, 2006) from the Adour estuary were found to be moderately contaminated with Hg species with numerous sources situated in the downstream urban area.…”
Section: Introductionmentioning
confidence: 99%
“…A form of waste that can be used for this purpose is municipal sewage sludge, the use of which for agricultural, non-agricultural, and soil remediation purposes is contingent on the identification of its physical, chemical, and microbiological properties [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, thanks to significant advances in the analysis and detection of trace contaminants, emerging contaminants have also been detected in plants (due to soil and water pollution), food products, living organisms and protected species (e.g., birds, polar bears), even in areas where there is no human activity (Datta et al 2018;Routti et al 2019). This demonstrates their uncontrolled Gwenzi et al 2018;Matich et al 2019;Mezzelani et al 2018;Pedrazzani et al 2019;Xu et al 2019 Endocrine disrupting compounds Różalska et al 2015;Ma et al 2016;Murdoch and Sanin 2016;Tuan Omar et al 2016;Archer et al 2017;Acir and Guenther 2018;Dong et al 2018;Gogoi et al 2018;Liu et al 2019;Ng et al 2019;Olaniyan et al 2020;Patel et al 2020 Environmental fate Cavalheiro et al 2017;Monneret 2017;Priac et al 2017;Archundia et al 2018;Koumaki et al 2018;Reichert et al 2019;Yu et al 2019 Exposure pathways Chokwe et al 2017;Koba et al 2018;Mearns et al 2018;Li et al 2019b;Routti et al 2019;Wu et al 2020b;Xiao et al 2020 Fate Eggen andVogelsang 2015;Katsigiannis et al 2015;Noutsopoulos et al 2015;Carr et al 2016;…”
Section: Introductionmentioning
confidence: 99%